7m+4n-3m+7n=

Simple and best practice solution for 7m+4n-3m+7n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7m+4n-3m+7n= equation:


Simplifying
7m + 4n + -3m + 7n = 0

Reorder the terms:
7m + -3m + 4n + 7n = 0

Combine like terms: 7m + -3m = 4m
4m + 4n + 7n = 0

Combine like terms: 4n + 7n = 11n
4m + 11n = 0

Solving
4m + 11n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-11n' to each side of the equation.
4m + 11n + -11n = 0 + -11n

Combine like terms: 11n + -11n = 0
4m + 0 = 0 + -11n
4m = 0 + -11n
Remove the zero:
4m = -11n

Divide each side by '4'.
m = -2.75n

Simplifying
m = -2.75n

See similar equations:

| x/-19=-2 | | (7x+2)-(2x^2+6x+8)= | | 4*5=585 | | 2*3=290 | | (3x^2-7x+2)+(4x^2+5x+5)= | | 28-4x=156 | | 3j-(j-4)+3= | | y=arcsin(x+2) | | -12x=-70 | | 4x-7=3.8 | | 5x+4x=70 | | 6(x-3)-4x=32 | | 4(-3.4)+1/3=(-3.4)-5/2 | | 0.03x-0.4x=2.85 | | a+0.8=-0.8a+3.86 | | 28+4x=156 | | -10=8x-3 | | 4(x+2)-6x+4=-42 | | 2+x=58 | | (-a^2+2)-(a^2-4)+(6a^2-5a*3)= | | 5x+140= | | .7=.35 | | 4s-12=5s+15 | | (4x^2+9x-2)+(4x^2+4x+19)-(8x^2-14)= | | 3(2x-1)=3x+1/2 | | 8K+1-1=17 | | 3(12-x)+6x=10 | | x+4=5x-20 | | 96=3(4x-8) | | 5(m-4)+6m=5(m+3)-7 | | -10x^2+6x+3=0 | | 2(3x+4)+2x=11x-4+x |

Equations solver categories